1981
DOI: 10.1136/vr.109.6.112
|View full text |Cite
|
Sign up to set email alerts
|

A re-examination of the role of Campylobacter fetus subspecies coli in enteric disease of the pig

Abstract: Campylobacter fetus subspecies coli was isolated from the small intestines of 17 piglets less than six weeks of age submitted for diagnosis. Sixteen of these animals had enteritis and in five of them no other probable bacterial cause of the enteric lesions was identified. Changes including congestion of the small intestinal mucosa, reduction in the height of the villi, thickening of the terminal ileum and histological evidence for inflammatory change in the small intestine were seen at post mortem examination.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…The present study confirms previous observations of Campylobacter-associated enteric disease in young piglets (31) and supports their use in investigating virulence factors associated with C. jejuni. The application of infecting this host with defined mutant strains, such as those deficient in invasin antigens, can clarify some of the mechanisms involved in the pathogenicity of C. jejuni.…”
Section: Discussionsupporting
confidence: 91%
“…The present study confirms previous observations of Campylobacter-associated enteric disease in young piglets (31) and supports their use in investigating virulence factors associated with C. jejuni. The application of infecting this host with defined mutant strains, such as those deficient in invasin antigens, can clarify some of the mechanisms involved in the pathogenicity of C. jejuni.…”
Section: Discussionsupporting
confidence: 91%
“…Such a clear difference was not observed in cattle and sheep. Taylor & Olubumni (1981) concluded that C. coli may be a cause of enteritis in pigs, and these findings support this view.…”
Section: Effect Of Enrichment Culturementioning
confidence: 58%
“…The different management regimes and the frequent introduction of new animals to the pig-rearing unit may in part explain this phenomenon. The conflicting results of experimentally infecting pigs with C. cli reported by different countries (1,2,6,23,34,35) could possibly be explained by the fact that different strains, which had various degrees of pathogenicity, were used. BRENDA typing could be used to more precisely identify such strains.…”
Section: Discussionmentioning
confidence: 99%